A new subfamily of Trichoceridae (Diptera: Tipulomorpha) from Early Cretaceous Lebanese amber - Shcherbakov, Dmitry E.; Azar, Dany (Zootaxa, 2019)
The first find of Trichoceridae in the Mesozoic of Gondwana and in Cretaceous ambers worldwide, Ewaurista pusilla gen. et sp. nov. is separated into Ewauristinae subfam. nov. demonstrating some venational traits in common with Limoniidae and a peculiar sexual dimorphism. The diagnosis of Trichoceridae is emended, and relationships of the family are discussed.